Sukanasa or Sukanasi (a part of the shikhara) - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These are assembled to form the jagati (raised platform), hence they are not in their original position. This fragment, for example, known as sukanasa (or sukanasi), was part of the shikhara, located above the entrance to the garbhagriha or inner shrine. The sukanasa (or sukanasi) is usually featured above the entrance to the garbhagriha or inner shrine and often contains the figure of the presiding deity to which the temple is dedicated (missing in this sukanasa). The corners of the arch have inverted conch motifs. The top of the arch has an elaborate kalapavriksha (tree of life) motif.